Early predictors of acute kidney injury in COVID‐19 patients. Issue 6 (9th February 2021) - Yildirim, Cigdem; Ozger, Hasan Selcuk; Yasar, Emre; Tombul, Nazrin; Gulbahar, Ozlem; Yildiz, Mehmet; Bozdayi, Gulendam; Derici, Ulver; Dizbay, Murat
Abstract: Aim: This study aims to determine the frequency of COVID‐19 related AKI and to identify the early predictors of AKI. Methods: This study is a single‐center, retrospective, observational study. Hospitalized COVID‐19 patients between 24/03/2020 and 31/05/2020 were included in the study. All patients were evaluated for renal dysfunctions with urine dipstick, protein/creatinine ratio, albumin/creatinine ratio in spot urine, serum cystatin C, serum creatinine level on hospital admission, and 28th day of hospital admission. To assess the utility of these parameters to predict AKI, a receiver‐operating characteristic curve was generated and the area under the curve (AUC) was calculated. Results: 348 patients were included. The average incidence of AKI was 4.9% (n = 17). The incidence of AKI in mild, moderate and severe COVID‐19 cases was 1.3% (n = 4), 9.0% (n = 3) and 76.9% (n = 10), respectively. Proteinuria was detected in 7.8% (n = 27) of patients with a urine dipstick test. In spot urine analysis, proteinuria was found in 20.1% (n = 70) of patients. The frequency of persistent proteinuria was 5.2% (n = 18). The AUC alue of serum cystatin C, D‐dimer and albumin/creatinine ratio to predict COVID‐19 related AKI were 0.96 (0.90 to 1.0), 0.94 (0.89–0.98), and 0.95 (0.91–0.98). Conclusion: In COVID‐19 patients with normal serum creatinine levels on hospital admission, albuminuria, serum cystatin C and D‐dimer levels may be an early predictor of COVID‐19 related AKI and these patients should be monitored closely for AKI. Since the sample size in the AKI group was small, our study results should be confirmed with larger cohort studies. SUMMARY AT A GLANCE: This observational single‐center study assessed the frequency and predictors of acute kidney injury in 348 hospitalized patients with COVID‐19. In this cohort, AKI was diagnosed in 4.9% of patients and proteinuria (spot urine analysis) in 20%. Albuminuria/creatinine ratio, cystatin C‐ and D‐dimer were identified as potential predictors of AKI on admission.